Prognostic Implication of Patient Age in H3K27M-Mutant Midline Gliomas - Vuong, Huy Gia; Ngo, Tam N. M.; Le, Hieu Trong; Jea, Andrew; Hrachova, Maya; Battiste, James; McNall-Knapp, Rene; Dunn, Ian F. (Frontiers in Oncology, 2022)
Introduction Pediatric and adult H3K27M-mutant midline gliomas have variable clinical presentations, prognoses, and molecular backgrounds. In this study, we integrated data from published studies to investigate the differences between these two groups. Methods PubMed and Web of Science were searched for potential data. Studies were included if they had available individual participant data on patients age of H3K27M-mutant midline gliomas. For time-to-event analyses, Kaplan-Meier analysis and Cox regression models were carried out; corresponding hazard ratios (HR) and 95% confidence intervals (CI) were computed to analyze the impact of age and clinical covariates on progression-free survival (PFS) and overall survival (OS). Results We included 43 studies comprising 272 adults and 657 pediatric midline gliomas with H3K27M mutation for analyses. In adults, there was a male predilection whereas females were slightly more common than males in the pediatric group. Spinal cord tumors were more frequent in adults. The prevalence of H3.1 K27M mutation was significantly higher in the pediatric cohort. Compared to adult patients, pediatric H3K27M-mutant midline gliomas exhibited more aggressive features including higher rates of pathologic features of high-grade tumors and Ki67 proliferation index, and had a shorter PFS and OS. Genetically, ACVR1 mutations were more common whereas MGMT methylation, FGFR1, and NF1 mutations were less prevalent in the pediatric cohort. Conclusion Pediatric H3K27M-mutant midline gliomas were demographically, clinically, and molecularly distinct from adult patients, highlighting an opportunity to refine the risk stratification for these neoplasms.